2022
DOI: 10.3390/polym14235296
|View full text |Cite
|
Sign up to set email alerts
|

Polyesters Incorporating Gallic Acid as Oxygen Scavenger in Biodegradable Packaging

Abstract: Biodegradable polyesters polybutylene succinate (PBS) and polybutylene adipate-co-terephthalate (PBAT) were blended with gallic acid (GA) via cast extrusion to produce oxygen scavenging polymers. The effects of polyesters and GA contents (5 to 15%) on polymer/package properties were investigated. Increasing GA formed non-homogeneous microstructures and surface roughness due to immiscibility. GA had favorable interaction with PBAT than PBS, giving more homogeneous microstructures, reduced mechanical relaxation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Eco-friendly packages can serve the purpose of sustainable food protection [ 15 ]. Food packaging is mainly utilized as a single-usage wrap and this triggers the waste generated by the plastic packaging industry.…”
Section: Introductionmentioning
confidence: 99%
“…Eco-friendly packages can serve the purpose of sustainable food protection [ 15 ]. Food packaging is mainly utilized as a single-usage wrap and this triggers the waste generated by the plastic packaging industry.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, other studies reported that multilayer structures with PE or PP as inner layers limited their biodegradability compared to the films developed in the present study, which are completely water-based. 27,60,67…”
Section: Biodegradability Of the Developed Filmmentioning
confidence: 99%
“…The most common examples reported in the literature are plant-/bio-based materials. Plant-based compounds such as gallic acid 25 are incorporated in biodegradable matrices like chitosan, 26 poly(butylene adipate-co-terephthalate) (PBAT) poly(butylene succinate) PBS matrices, 27 and thermoplastic cassava starch 28 to use as an oxygen scavenging system in food packaging applications. Jain et al , 2024, developed an Acacia Catechu /calcium carbonate, 29 and Kumar et al , 2023 resorcinol/potassium carbonate 14 -based oxygen scavenging system with a moisture activation mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Food packaging must also control the transfer of water vapour, oxygen and/or carbon dioxide, which impact rates of oxidation, microbial development and physiological reactions of food degradation. Plastics are commonly permeable to small volatiles such as gases (O 2 , CO 2 ), water vapour, organic vapours and liquids [ 88 , 89 ] and water absorption barrier properties are essential basic requirements when packing food. The moisture barrier property is important in food packaging as this preserves the texture in both dry and moist food and controls microbial growth of aerobic spoilage.…”
Section: Natural Fibres In Packagingmentioning
confidence: 99%